Examining students' cognitive processes in solving algebraic numeracy problems: A Phenomenology study - Monika Agnes Henny Kinanti; Imam Sujadi; Diari Indriati; Krida Singgih Kuncoro (Universitas Hamzanwadi, 2023)
Problem-solving can be understood as a cognitive process in which students know facts, processes, concepts, and procedures and then apply the knowledge to solve problems in real situations. Indonesia’s national average achievement of numeracy skills in 2021, the cognitive process of competence reasoning is higher than the competencies of knowing and applying. This study aims to analyze students' cognitive processes in solving numeration problems related to the algebraic domain. The algebraic domain in this study is limited to competencies in making generalizations from patterns in number sequences and object configuration sequences. This research was conducted qualitatively with a phenomenological design using three high-category and three low-category students to achieve data saturation. The supporting instruments are students' answers and interview results related to the algebraic domain. This study concluded that students' cognitive processes in solving numeracy problems associated with the algebraic domain in the high and low categories have different descriptions. This difference in intelligence has an impact when solving math problems. This research can help enrich the understanding of students' cognitive processes and contribute to the development of better mathematics learning strategies and curricula.